La sucesión de Carlos II y las Cortes de Castilla - García-badell Arias, Luis María (Cuadernos de Historia del Derecho, 2007)
The importance reached by the “Commission of Millions” in the Castilian Crown at the end of the 17th century, left in background the Cortes and limited its institutional evolution. The succession of Carlos II demonstrated to what extent the atrophy had reached the Castilian representative institutions. The possible call of Cortes of Castile was then just another tactical instrument used by the opposing factions to favor their cause, but it was never considered as a substantive question with decisive political consequences.